Isolated cystic tuberculosis of medial cuneiform: a case report - Ali, Nadeem; Bhat, Abedullah; Muzzafar, Khalid; Fatima, Akeela (International Journal of Research in Medical Sciences, 2017)
Isolated tuberculosis of foot is a rare entity. Plenty of literature is available on osteoarticular tuberculosis but literature on tuberculosis of foot is limited. Additionally the condition mimics variety of other foot pathologies which can delay diagnosis and add to morbidity. We present a twelve year old boy who presented clinically with swelling, pain and discharging sinus of foot with a cystic lesion in medial cuneiform on radiography. Though histopathology and Ziehl Nielsen staining later on established the diagnosis, but initially it was mistaken as a case of mycotic osteomyelitis. Tuberculosis of foot, though rare, should always be one of the differential diagnoses in a patient presenting with bony lesion on radiography irrespective of absence of constitutional symptoms and negative tests for tuberculosis. If battery of tests fails to establish diagnosis, open biopsy with curettage and histopathology should be considered to work out the final diagnosis.